Live Donor Kidney Transplant Outcomes Till February 2018 in the First Kidney Transplant Center in Ethiopia. (July 2018) - Siyoum, Mekdim; Ahmed, Momina M; Bekele, Mahteme; Abebe, Engida; Berhe, Tekleberhan; Worku, Birhanu; Redae, Berhane; Abebe, Zerihun; Tedla, Fasika; Abate, Mersema; Jayaram, Deepa; Pestana, Jose Medina; et al.
Abstract : Background: Kidney transplantation is the preferred treatment for patients with end stage renal failure in industrialized countries, but its availability is very limited in Sub-Saharan Africa. In Ethiopia, this option was accessible for only those few who could afford to travel abroad with their living donors for donation and transplantation. In collaboration with faculty from the University of Michigan (UM), the Federal Democratic Republic of Ethiopia, National Kidney Transplant Center, the first Ethiopian kidney transplant program, was launched at Saint Paul's Hospital Millennium Medical College (SPHMMC) in Addis Ababa in Sept 2015. This study reports on live donor and recipient kidney transplant outcomes to date. Methods: This is a retrospective cross sectional qualitative study of live kidney transplant performed at Saint Paul Hospital Millennium Medical College. Results: This study reports on live donor and recipient kidney transplant outcomes to date. From September 2015 through February 2018, a total of 70 live kidney transplants were performed at Saint Paul's Hospital Millennium Medical College (SPHMMC). All procedures were performed by SPHMMC transplant team in collaboration with University of Michigan faculty and later experiences from Hospital Do Rim Sao Paulo Brazil was incorporated. All of recipients were 1st time recipients HLA typing and crossmatch were performed off site B and T cell crossmatch were negative by the CDC method in all patients None of the recipients have significant titer of Anti-HLA antibodies. Majority of donors were females (53.8%) and majority of recipients were males (60%). Donor age ranged from18 to 66 with a mean of 30.2 years. Mostly donors were siblings (40%) or parents (12%) of the recipient. Donor Outcomes: 47 were initially hand assisted Laparoscopic nephrectomies (one conversion) with conversion rate of 6.7 % (due to intraperitoneal adhesions ), the remaining twenty three were open donor nephrectomi with after an experience sharing at hospital Do rim in Brazil(a mini-incision ( 10 cm) open donor nephrectomy technique has been utilized). There was 100% survival, two re -hospitalization for lymphocele. 1 donor complication – Heamopneumothorax, and Small bowel obstruction requiring exploration, Prolonged hospital stay (14 days) and another with major bleeding during open donor nephrectomy. Recipient Outcome: There was only one hyper-acute rejection and four graft censored death one having superficial surgical site infection and one suffering from Atelectasis. Conclusion: Despite challenges arising from a resource-limited setting, outcomes of Living Donor Kidney Transplantations (LDKT) performed at SPHMMC are comparable to international standards. Blending experiences from different countries and evolving into a more suitable contextual implimentation of LDKT makes the prospects for sustainable Living Donor Transplantation in Ethiopia are promising. Ethiopian Mistry of Health.